Effectiveness of some selected insecticides and botanicals against okra shoot and fruit borer (Bangladesh Journal of Agricultural Research, 2017)
An experiment was conducted to evaluate the effectiveness of some selected insecticides and botanicals against okra shoot and fruit borer Earias vittella F. under field conditions. The insecticides tested were Relothrin 10EC @ 1ml l-1, Marshal 20EC @ 2ml l-1and Riva 2.5 EC @ ml l-1; and the botanicals were NSKE @ 50g l-1, Neem leaf extract @ 100g l-1 and Bishkatali leaf extract @ 100g l-1. An additional treatment of Mechanical control (hand picking) and an untreated control were maintained in the experiment for comparison. All treatments were applied at 15 days interval. Shoot infestation was the lowest in Marshal 20EC treated plot (4.34% at pre-fruiting and 3.55% at fruiting stage) and the highest was in untreated control plot (21.4%). The lowest fruit infestation by okra shoot and fruit borer was obtained with Marshal 20EC (5.07% n/n and 3.65% w/w) followed by Relothrin 10EC (5.43% n/n and 4.27% w/w) and the highest infestation was observed under untreated control plot (19.67% n/n and 19.81% w/w). The reduction of fruit infestation over untreated control ranged from 56.93-81.55% by number and 43.47-74.22% by weight. The highest marketable yield (10.46 t ha-1) was obtained in Marshal 20EC treated plot followed by in Relothrin 10EC 10.30 t ha-1 with the maximum benefit cost ratio (BCR) 6.72.Bangladesh J. Agril. Res. 42(2): 353-362, June 2017